Methods and Means to Order the Organizations’ Workload by Prioritizing Time Management - Kharkheli, Manana (European Scientific Journal, ESJ, 2020)
Every person wishes to have a high-quality life and every business wishes to achieve its business goals. At the same time, all these are in causeeffect relations: we achieve what we are concentrated on and we gain the results, what we create the reasons for. An important role in our existence and achievement of success in modern world is played by the rational distribution and right management of time. This important skill is to be developed from an early age, surely if we wish to be as much efficient and useful as possible. Time is limited and a human, who is able to manage time correctly, manages and controls all his life. Therefore, we must use the limited time of our lives rationally and not waste it in vein. The rhythm of life is fast and we permanently experience time deficit. This is why we are unable to do all the things we plan in our minds. In this case we must use time management. Successful people are productive. They work much and achieve much. Productivity, first of all, means the outcome, not the process. People waste time, as they have not decided whether or not to increase their productivity. The major secret of time management lies in the concentration and purposefulness. Start with solving the first objective on the list and continue with other objectives in the given order.